Adipose-derived mesenchymal stem/stromal cells: from the lab bench to the basic concepts for clinical translation - Frontini López, Yesica Romina (2018)
In the last years, much work has shown that the most effective repair system of the body is represented by stem cells, which are defined as undifferentiated precursors that own unlimited or prolonged self-renewal ability, which also have the potential to transform themselves into various cell types through differentiation.All tissues that form the body contain many different types of somatic cells, along with stem cells that are called ‘mesenchymal stem (or stromal) cells’ (MSC). In certain circumstances, some of these MSC migrate to injured tissues to replace dead cells or to undergo differentiation to repair it.The discovery of MSC has been an important step in regenerative medicine because of their high versatility. Moreover, the finding of a method to isolate MSC from adipose tissue, so called ‘adipose-derived mesenchymal stem cells’ (ASC), which share similar differentiation capabilities and isolation yield that is greater than other MSC, and less bioethical concerns compared to embryonic stem cells, have created self-praised publicity to procure almost any treatment with them. Here, we review the current techniques for isolation, culture and differentiation of human ASC (hASC), and describe them in detail. We also compile some advantages of the hASC over other stem cells, and provide some concepts that could help finding strategies to promote their therapeutic efficiency.